BYL719 (alpelisib) for the treatment of PIK3CA-mutated, recurrent/advanced cervical cancer. Issue 2 (April 2023) - Bogani, Giorgio; Chiappa, Valentina; Bini, Marta; Ronzulli, Dominique; Indini, Alice; Conca, Elena; Raspagliesi, Francesco
Purpose: Advanced/recurrent cervical cancer has limited therapeutic options, with a median progression-free survival after the failure of systemic treatments ranging between 3.5 and 4.5 months. Here, we reported our preliminary experience in the use of BYL719 (alpelisib) in advanced/recurrent cervical cancer after failure of at least 2 lines of treatment. The Istituto Nazionale dei Tumori di Milano approved this investigation. Methods: From April 2020 to September 2020, 17 consecutive patients with recurrent cervical cancer had Next Generation Sequencing (NGS). Of these, six patients harboring the PIK3CA mutation were included in the study. All patients had been treated with at least 2 previous lines of systemic treatment: 3 patients received >2 prior lines of treatment in the recurrent or metastatic setting; 60% had received prior bevacizumab in combination with chemotherapy. All patients started alpelisib at the daily dosage of 300 mg. Results: Investigator-assessed confirmed objective response rate (ORR) was 33%. The disease control rate (DCR) was 100%. According to RECIST 1.1, two patients had a partial response (PR), and four patients had stable disease (SD). No complete response was observed. The mean duration of response (DOR) was 11.5 (SD 3.75) months; five patients had PR lasting for >9 months. One patient stopped the treatment at 0.82 months due to the onset of a grade 2 adverse event (AE) (skin rash). Grade 3 treatment-related AEs included: lymphoedema (n = 1, 17%) and rash (n = 1, 17%). No treatment-related grade 4-5 AEs occurred. Conclusions: Our preliminary data highlighted a high level of efficacy in this setting of patients. Further trials are needed to assess the safety and effectiveness of alpelisib in PIK3CA-mutated recurrent/advanced cervical cancer.